FAKTOR FAKTOR YANG MEMPENGARUHI PERILAKU BELANJA WANITA PADA SUPERMARKET DI KOTA MEDAN - Amrin Mulia Utama Nasution (Universitas Medan Area, 2017)
The problem in this research is to find how far the influence of the price, product, services, and psychology of the shopping behaviour of women at Supermarket in Medan. The objective of this research is to find how the price, product, services, and psychology of the shopping behaviour of women at Supermarket in Medan. The primary data collection is using questionaire for the women who shopping more than twice. The data analysis method is quantitative descriptive with linier double regresion. The results showing us that product, price, services and psychology have positive influence and significant to the women shopping behaviour at Supermarket in Medan. Partially, the product is the most influence variable for the shopping behaviour at Supermarket in Medan.Keywords : product, price, service, psycology, behaviour